The Effect of Safety Training Intervention on Safety Climate Among the Operational Staff of West Oil and Gas Company - Mohammad Reza Omidi; Meysam Jafari Eskandari; Nabi Omidi (Health in Emergencies & Disasters Quarterly, 2021)
Background: The safety climate shows the attitude and general perception of the organization’s management regarding safety. This study investigates the impact of safety training on the safety climate of operational employees working in the West Oil and Gas Company. Materials and Methods: This study is quasi-experimental interventional research, which was conducted in the first half of 2019 in West Oil and Gas Production Company with a pretest-posttest design. The study population included all workers in the operational departments of The West Oil and Gas Production Company. The sampling was done randomly with 240 people. The study questionnaire included a demographic information questionnaire and the safety climate questionnaire of “the safety organization of England.” The validity of the questionnaire was confirmed by safety professors, and its reliability was obtained at 0.84 using the Cronbach α coefficient. Results: The mean score of safety climate components before the intervention was 2.65, and after the educational intervention reached 3.66. The safety improvement had the highest score among the components of the safety climate. Also, the lowest mean score of the component before the intervention was related to the violation of safety rules, which had the lowest mean score after the intervention of the licensing system. Conclusion: Educational intervention improved the safety climate in West Oil and Gas Production Company, so safety training plays a vital role in increasing the safety climate in the oil and gas industries.